Towards equitable and sustainable indoor air quality guidelines − A perspective on mandating indoor air quality for public buildings - Ulla Haverinen-Shaughnessy; Marzenna R. Dudzinska; Samy Clinchard; Sani Dimitroulopoulou; Xiaojun Fan; Piet Jacobs; Henna Maula; Amelia Staszowska; Oluyemi Toyinbo; Ju-Hyeong Park (Indoor Environments)
A recent article published in Science urges mandatory indoor air quality (IAQ) standards in public spaces, focusing on protecting public health, especially against diseases such as COVID-19, but also IAQ in general (1). Given the significance of this topic to our society, this short communication aims to provide commentary on the article and further discuss the importance of establishing IAQ standards. Citing a lack of legislated standards globally, the authors (1) propose numerical limits for four IAQ parameters: particulate matter (PM2.5), carbon dioxide (CO2), carbon monoxide (CO), and ventilation rate (VR). While recognizing that most of the countries do not have any mandatory IAQ standards, it is also noteworthy that IAQ regulations or guidelines exist in more than 40 countries. We like to emphasize that successful IAQ management requires recognizing, sharing, and reviewing openly available, existing regulations and guidelines, while adapting them to regional characteristics.